Analiza potreb po uporabi simulacij v procesu vseživljenjskega učenja medicinskih sester - Žvanut, Boštjan (Obzornik zdravstvene nege, 2013)
Introduction: Simulations are used in both formal and informal training of health professionals as an active teaching and learning method. In Slovenia, however, simulation-based medical training has not been widely accepted and used in spite of the benefits and opportunities it can offer. The aim of the study was to identify the types of simulations that nurses responsible for nurse education find interesting and useful. Methods: The survey took place from November 30 to December 24, 2010. Leading nurses from primary, secondary and tertiary levels of healthcare and social welfare institutions participatedin the study. The final sample included 78 respondents. Among the 146 simulations divided into 11 sets, the respondents selected those which aremost useful and relevant enough to be included in the lifelong learning programs. For the data analysis univariate analysis and Chi-square test were used. Results: Results of the study showed great interest in simulations of conditions that require urgent treatment of patients, particularly the simulation Use of automated external defibrillator in the event of cardiac arrest (62.8 %). Statistically significant interest was expressed by the participants from the primary (I) and tertiary (III) levels of healthcare for the following simulations: Acute allergic reaction (I: 69 %, III: 67 %, p = 0,036), Supraventricular tachycardia (I: 73 %, III: 56 %; p = 0.02), and Ventricular fibrillation and ventricular tachycardia (teamwork) (I: 73 %, III:50 %; p = 0.014). Discussion and conclusion: As relatively high level of interest is shown for the simulation-based education and training, it would be reasonable to introduce this learning/teaching method into nursing undergraduate curricula and lifelong learning programmes. The different interests identified should be taken into consideration when developing nursing training courses and programmes.
Keywords: health care; lifelong learning; medicinske sestre; nursing care; simulacija; simulation; vseživljenjsko učenje; zdravstvena nega; zdravstvo